Screening for pre‐eclampsia using sFlt‐1/PlGF ratio cut‐off of 38 at 30–37 weeks' gestation. (5th December 2016) - Dragan, I.; Georgiou, T.; Prodan, N.; Akolekar, R.; Nicolaides, K. H.
ABSTRACT: Objective: To evaluate a soluble fms‐like tyrosine kinase‐1 (sFlt‐1) to placental growth factor (PlGF) ratio cut‐off of 38 for the prediction of pre‐eclampsia (PE) in routine assessment in singleton pregnancies at 30–37 weeks' gestation. Methods: This was a prospective observational study in women attending a third‐trimester ultrasound scan at 30–37 weeks as part of routine pregnancy care. Serum sFlt‐1 and PlGF were measured and their ratio was calculated. We estimated the detection rate (DR), false‐positive rate (FPR), positive predictive value (PPV) and negative predictive value (NPV) of sFlt‐1/PlGF ratio >38 for the prediction of delivery with PE at < 1, < 4 and ≥ 4 weeks after assessment. Results: The study population of 12 305 singleton pregnancies was examined at a median of 32.4 (range, 30.0–36.9) weeks and included 14 (0.11%), 77 (0.63%) and 227 (1.84%) cases that subsequently delivered with PE at < 1, < 4 or ≥ 4 weeks' after assessment, respectively. The DR, FPR, PPV and NPV of sFlt‐1/PlGF ratio > 38 in the prediction of delivery with PE at < 1 week were 78.6%, 4.5%, 1.9% and 99.97%, respectively; the values for delivery with PE at < 4 weeks were 76.6%, 4.1%, 10.4% and 99.85% and for delivery with PE ≥ 4 weeks were 20.7%, 4.3%, 8.3% and 98.47%. Conclusion: In routine screening of singleton pregnancies, the performance of a sFlt‐1/PlGF ratio > 38 is modest for the prediction of delivery with PE at < 1 and at < 4 weeks after assessment and poor for the prediction of delivery with PE at ≥ 4 weeks after assessment. A sFlt‐1/PlGF ratio > 38 predicted 79% of cases delivering with PE at < 1 week after assessment, at a FPR of 4.5%; consequently, a policy of hospitalizing patients with a ratio > 38 would potentially lead to unnecessary hospitalization in 4.5% of pregnancies and a ratio of ≤ 38 would falsely reassure one fifth of women who will deliver with PE within 1 week of assessment. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.